Analisa Keandalan Gardu Induk Di PT. Chevron Pacific Indonesia Area 6D Substation Minas - Tetti Silalahi; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The level of Analysis system reliability substations, with data Analysis disturbance and recorded from the PT.CPI it will be calculated level of reliability. Needed data in order to continue the analysis of the reliability of the system substation data is current as trip interruption, Repair, and natural disturbances that occurred at the substation 6D Minas, based on data from the existing problems will be known level of reliability in substation 6D Minas PT. Chevron Pacific Indonesia. Analysis using the formula of probability and simulation Etap 12.6.0 Transformer # 1 has a value of 2.0271 SAIDI hours / year and transformer # 2 has a value of 2.1148 SAIDI hours / year and transformer # 1 has a value SAIFI 1,197 times / year while the transformer # 2 has SAIFI value of 2.486 times / year. Feeder # 1 has a value of SAIDI 0559 hours / year, Feeder # 2 has a value of SAIDI 0852 hours / year, Feeder # 3 has a value of SAIDI 0294 hours / year, Feeder # 4 has a value of SAIDI 1,000 hours / year, Feeder # 5 has a value of SAIDI 1,642 hours / year, Feeder # 6 has a value of SAIDI 0000 hours / year. Feeder Minas 6D so as to have a value of SAIDI 0724 hours / year of SAIFI standard IEEE Std. 1366-2000Key words: Etap 12.6.0, reliability, Electric power system, substation